A microscope in your pocket: can smartphones be used to perform microsurgery? - de Menezes Neto, Balduino Ferreira [UNESP]; Magnani, Lucas Vannuchi [UNESP]; Fernandes, Matheus Scuracchio; Brunello, Luis Fernando Spagnuolo [UNESP]; de Souza, Thales Fernandes [UNESP]; Viterbo, Fausto [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: To evaluate the use of the latest generation smartphone camera in performing arterial microanastomosis in rats. Methods: Ten Wistar rats were divided into 2 groups and underwent anastomosis of the right carotid artery with the aid of magnification from a microscope (group M) and a smartphone camera (group S), to compare patency in 72 hours, as well as to measure the weight of the animals, diameter of the carotid arteries and anastomosis time. Results: There was no statistical difference between the weight of the animals or the diameter of the carotid arteries. There was a statistical difference for the time spent on anastomoses, which was greater in group S, with higher rates of thrombosis (p < 0.05). Conclusion: Although our patency and anastomosis time results were statistically lower in the smartphone group, there was success in some cases. As the segment continues to progress, it is likely that the results will improve in line with the evolution of camera technology.
Keywords: Anastomosis, Surgical; Microsurgery; Smartphone